CHALLENGES AND POSSIBLE SOLUTIONS IN DETERMINING INR - E. V. Titaeva; A. B. Dobrovolsky («REMEDIUM GROUP» Ltd., 2015)
Despite the development of new oral anticoagulants, vitamin K antagonists (VKA) continue to be widely used for the treatment and prevention of throm-boembolic complications. On top of that, they have no alternative in patients with artificial heart valves. Receiving AVC results in the synthesis of modified factors of pro-thrombin-converting complex (prothrombin, factor X, IX and VII, as well as two components of the anticoagulant system - protein C and protein S) without capacity to bind with the phospholipid surface, which significantly reduces the likelihood of intravascular thrombosis, but the degree of anti-coagulation is individual and requires monitoring for each patient. Prothrombin test (PT test) is used to monitor the degree of anti-coagulation, which is based on determining the plasma clotting time in a patient after addition of thromboplastin and calcium chloride (prothrombin time). Tromboplastin is animal tissue extract containing tissue factor and phospholipids. In practice, the determination of the anti-coagulation degree by prothrombin time is no easy task. The fact of the matter is that various thromboplastin drugs have different sensitivity to the reduction of factors of prothrombin-converting complex; clotting time of normal and pathologic plasma depends on used thromboplastin and differs even for different series of thromboplastin supplied by the same manufacturer. In addition, prothrombin time depends on the method used (coagulometer). WHO had adopted a system of reporting the PT test results in the form of INR (International normalized ratio) specifically to measure the degree of anti-coagulation in patients who receive oral anticoagulant therapy.